Administering an appeasing substance to optimize performance and health responses in feedlot receiving cattle. (17th October 2020) - Colombo, Eduardo A; Cooke, Reinaldo F; Brandão, Alice P; Wiegand, Jacob B; Schubach, Kelsey M; Duff, Glenn C; Gouvêa, Vinícius N; Cappellozza, Bruno I
Abstract: This experiment evaluated the impacts of administering a bovine appeasing substance (BAS ) at feedlot entry to receiving cattle. Angus-influenced steers ( n = 342) from 16 sources were purchased from an auction yard on day –1, and transported (12 hr; 4 trucks) to the feedlot. Upon arrival on day 0, shrunk body weight (BW; 240 ± 1 kg) was recorded and steers were ranked by load, shrunk BW, and source and assigned to receive BAS (IRSEA Group, Quartier Salignan, France; n = 171) or placebo (diethylene glycol monoethyl ether; CON ; n = 171). The BAS is a mixture of fatty acids that replicate the composition of the bovine appeasing pheromone. Treatments (5 mL) were topically applied to each individual steer on their nuchal skin area. Steers were allocated to 1 of 24 drylot pens (12 pens/treatment) and received a free-choice diet until day 46. Steers were assessed daily for bovine respiratory disease (BRD ) signs, and feed intake was recorded from each pen daily. Steer unshrunk BW was recorded on days 7, 17, 31, 45, and 46. Shrunk BW on day 0 was added an 8% shrink to represent initial BW, and final BW was calculated by averaging BW from days 45 and 46. Blood samples were collected from 5 steers/pen on days 0, 7, 11, 31, and 45. Pen was considered the experimental unit. Steer BW gain was greater ( P = 0.04) in BAS vs. CON (1.01 vs. 0.86 kg/d, SEM = 0.05). Feed intake did not differ ( P = 0.95) between treatments, resulting in greater ( P = 0.05) feed efficiency in BAS vs. CON (171 vs. 142 g/kg, SEM = 10). Plasma cortisol concentration was greater ( P = 0.05) and plasma glucose concentration was less in CON vs. BAS on day 7 (treatment × day; P = 0.07 and <0.01, respectively). Mean plasma β-hydroxybutyrate concentration was greater ( P < 0.01) in BAS vs. CON (3.23 and 2.75 mg/mL; SEM = 0.12). Incidence of BRD was greater ( P ≤ 0.05) in BAS vs. CON from days 6 to 10 and days 19 to 23 (treatment × day; P < 0.01), although overall BRD incidence did not differ ( P = 0.20) between treatments (82.4% vs. 76.6%, respectively; SEM = 3.2). A greater proportion ( P = 0.04) of BAS steers diagnosed with BRD required one antimicrobial treatment to regain health compared with CON (59.3% vs. 47.6%, SEM = 4.2). Hence, BAS administration to steers upon feedlot arrival improved BW gain during a 45-d receiving period by enhancing feed efficiency. Moreover, results suggest that BAS improved steer performance by facilitating early detection of BRD signs, lessening the disease recurrence upon first antimicrobial treatment.